Infection control personnel and implementation of infection control measures in Hungarian long-term care facilities: national results from a European-wide survey - Szabó, Rita (International Journal of Infection Control, 2014)
Infections in long-term care facilities (LTCFs) are important public health concerns, but data are limited on how these facilities are working to prevent and control infections in Hungarian long-term care facilities (LTCFs). For this reason, in 2003, the National Center for Epidemiology (NCE) joined a European-wide survey to determine the current infection control practices and education needs in LTCFs. Self-administered questionnaire was sent to all participating LTCFs. Local surveyor completed the paper-based questionnaire. Descriptive statistics were used to present the data. In total, 91 LTCFs took part in this voluntary and anonym survey. The average number of LTCF beds was 102 with a range of 50 to 690 beds. Only 8.8% of LTCFs had assigned an infection control practitioner. 96.7% of LTCFs did not have an institutional surveillance programme and/or guidelines in place related to infection prevention and control. The number of full-time equivalent infection control practitioner is low (0.07 per every 250 residents). Our results emphasise the need the trained infection control practitioners and the implementation of infection prevention guidelines and programmes in order to protect vulnerable residents from preventable infections. Keywords: infection prevention and control, infection control practitioner, long-term care facility, infection, elderly